Design, Synthesis and Insecticidal Activity of Novel Phenylpyrazoles Containing a 2,2,2-Trichloro-1-alkoxyethyl Moiety - Zhao, Qiqi; Li, Yongqiang; Xiong, Lixia; Wang, Qingmin (Journal of agricultural and food chemistry, 2010)
A series of novel phenylpyrazoles containing a 2,2,2-trichloro-1-alkoxyethyl moiety were designed and synthesized via the key intermediate 5-trichloroethylideneimino-3-cyano-1-(2,6-dichloro-4-trifluoromethylphenyl)-4-alkylsulfenylpyrazole (5). The addition reaction of the imine 5 was closely related with the nature of the alcohol. The target compounds were confirmed by 1H NMR and elemental analysis. The results of bioassays indicated that the target compounds possessed excellent activities against a broad spectrum of insects such as bean aphid (Aphis craccivora), mosquito (Culex pipiens pallens) and diamondback moth (Plutella xylostella). Especially, the foliar contact activity against bean aphid of compound 7h at 2.5 mg kg−1 was 89%, the larvacidal activity against mosquito of compound 6c at 2.5 μg kg−1 was 100%, the activity against diamondback moth of compound 7a at 5 mg kg−1 was 87%, and all of these activities were much higher than the contrast ethiprole. The results of insecticidal activities showed that the two pairs of enantiomers 7d-1 and 7d-2 gave activities without distinctive difference, and it was the similar situation for 7e-1 and 7e-2. Interestingly, the target compounds exhibited high selectivity between diamondback moth and oriental armyworm, both of which are of the order Lepidoptera. The 2,2,2-trichloro-1-alkoxyethyl moiety was essential for high insecticidal activities.